Quantitative and rapid detection of microcystin-LR using time-resolved fluorescence immunochromatographic assay based on europium nanospheres. Issue 45 (9th November 2017) - Zhang, Yi; Ding, Xin-Liang; Guo, Ming-Ming; Han, Ting-Ting; Huang, Zi-Jian; Shang, Hong-Tao; Huang, Biao
Abstract : In the present study, a novel time-resolved fluorescence immunochromatographic assay was established for the rapid quantitative detection of microcystin-leucine arginine (MC-LR). Abstract : In the present study, a novel time-resolved fluorescence immunochromatographic assay was established for the rapid quantitative detection of microcystin-leucine arginine (MC-LR). In this method, the europium nanoshpere labelled with anti-MC-LR antibodies was used as the luminescent tracer, dissolved in the running buffer and then added with the sample solution on the pad. MC-LR-BSA and goat anti-mouse antibody were dispensed on the nitrocellulose membrane for the test and the control line, respectively. The optimal parameters were 0.05 g L −1 MC-LR-BSA, 1 : 100 colloidal europium–antibody conjugate, and 10 min reaction time. The linear working range for MC-LR was 0.1–5 μg L −1 with an IC50 of 0.78 μg L −1 and a sensitivity of 0.035 μg L −1 . The low cross-reactivity was observed with MC-YR and MC-LF. The assay accuracy was confirmed by the HPLC method with a correlation coefficient of 0.99. When the variable coefficients were 4.4% and 5.4%, the average recoveries of tap and lake water were 94.6% and 102.8%, respectively. The time-resolved fluorescence immunochromatographic assay provides a sensitive, simple, and speedy performance for MC-LR quantitative determination and has a potential use for water sample screening.